Research on Health and Thermal Comfort of Unit-Type Student Apartments in the Western China Science and Technology Innovation Harbor - Zanshe Wang; Yue Wu; Zhaoying Jia; Qi Gao; Zhaolin Gu (Frontiers Media S.A., 2022)
BackgroundIn China, the collective living mode of "multiple people living in one room" is widely used in college students' dormitories; the space environment has high personnel density and poor thermal comfort and healthy environment. The unit-type apartments were completed in the western China science and technology innovation harbor that considers personal independence and public activity spaces.AimThe purpose of this study is to explore the applicability, thermal comfort, healthy environment, and the correlation of influencing variables of the new unit-type apartment. Especially the influence of physical parameters on personal space under heating in winter and air conditioning in summer.MethodThe field investigations and questionnaires to conduct a personal study of architectural space, healthy environment, and thermal comfort were carried out, and the measurement tests of the building's physical environment were carried out in winter and summer semesters.ResultsThe questionnaires survey shows that the privacy of the unit apartment is satisfactory, and the independent learning and communication is increased. The field measurement results show that due to the narrow space of the private room, the floor radiant heating mode still forms a hot and dry thermal environment in winter, and the temperature fluctuates significantly after the air conditioner is turned on in summer.ConclusionsThe unit-type apartments align with young students' physiological and psychological characteristics and the behavioral aspects of postgraduates, with high comprehensive satisfaction up to 80%. However, the indoor thermal environment quickly fluctuates due to the narrow independent space. Moreover, 90% of the window ventilation ratio shows that it has become the main measure to actively regulate the indoor climate, which is beneficial to students' health but increases energy waste and further aggravates the fluctuation of the thermal environment. More refined regulations should be executed for heating in winter and air conditioning in summer.